Safety and feasibility of lapatinib for the treatment of a EGFR1/HER-2-positive advanced gastrointestinal stromal tumor in a cat - Holanda, André Gustavo Alves; Civa, Patrick Antônio Sonaglio; Fonseca-Alves, Carlos Eduardo [UNESP]; Dos Anjos, Denner Santos [UNESP] (Revista Brasileira de Medicina Veterinaria, 2025)
Gastrointestinal stromal tumors (GISTs) are uncommon mesenchymal tumors in cats that originate from interstitial cells of Cajal (ICC). ICCs are mesenchymal cells found within the muscle layers of the alimentary tract that facilitate communication between the autonomic nervous system and smooth muscles. In this case, lapatinib, a tyrosine kinase inhibitor (TKI) that targets EGFR1 and HER2, was used as part of precision therapy for metastatic GIST in an 8-year-old, 2.7 kg, spayed, female mixed-breed cat, guided by the high expression of these receptors in the tumor. The treatment resulted in partial remission of liver metastases, with a progression-free survival of 171 days and an overall survival of 192 days after starting lapatinib. Lapatinib was well tolerated, with minimal adverse gastrointestinal effects. These findings highlight the potential role of molecular profiling in guiding targeted therapy for feline GISTs and suggest that lapatinib may be a viable treatment option for EGFR1/HER2-positive tumors. Further studies are needed to evaluate the efficacy and safety of TKIs in veterinary oncology, as well as their impact on long-term survival and quality of life in feline patients with GISTs.